Planning the Development of Arctic Maritime Communications in the Era of Hybrid Warfare - Sergey Y. Kozmenko; Arina S. Kozmenko (Арктика и Север)
Russia’s regional presence in the Arctic is the dominant goal of the country’s national maritime policy and is ensured by the level of development of the Arctic communications system, while the primary significance from the standpoint of national security belongs to the maritime component of this system, including the Northern Sea Route (NSR), which has the status of a national transport artery. The importance of the Arctic among the national interests of the country is confirmed by the current Maritime Doctrine of Russia 2022 and other strategic planning documents of recent years. The development of Arctic maritime communications is planned within the current horizons up to 2030 and 2036, both in terms of ensuring cargo turnover of the NSR (as the axial framework of Arctic maritime communications) and in the context of approving capital construction activities and facilities. Besides, the subject of planning is the development of the fleet, including icebreakers and reinforced ice-class vessels, which are rightfully a symbol of Russia’s Arctic maritime potential. The presence of these vessels together with military ships on the NSR and sea communications of the Arctic Ocean (AO) and the Arctic seas ensure the connectivity and integrity (both maritime and territorial) of the Arctic regional space. Therefore, the replenishment of the Arctic ice fleet in accordance with the needs of large oil and gas projects is of critical importance, especially in the era of hybrid confrontation between Russia and the countries of the “collective West”, which has already acquired obvious features of a full-fledged war.